2020
DOI: 10.3390/ma13112442
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Pore and Microstructure Fractal Characteristics of Alkali-Activated Coal Gangue-Slag Mortars

Abstract: Just as it is regarding ordinary cement-based materials, the pore structure and microstructure of alkali-activated materials are disordered. It is essential to predict the macroscopic properties by studying the pore and microstructure fractal characteristics of materials. In this paper, the effects of slag content and alkali activator modulus on compressive strength, porosity, and microstructure of alkali-activated coal gangue-slag (AACGS) mortar were studied. Further, with the help of mercury intrusion porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These heterogeneities are uniformly distributed in the matrix and generated during the elaboration process probably due to the retention of air and water bubbles evaporating during the drying stage. Ma et al [2020] reported that, when slag is fully used as raw material, the increase in alkali content would lead to an increase in the characteristic pore size and a decrease in the total porosity. La concentration d'activateurs alcalins a également une grande influence sur les structures des pores en raison du changement de l'étendue de la géopolymérisation et de la teneur en eau [Chen et al, 2022].…”
Section: Effect Of Sludge Dewatered and Stabilized By Hydrated Lime O...mentioning
confidence: 99%
“…These heterogeneities are uniformly distributed in the matrix and generated during the elaboration process probably due to the retention of air and water bubbles evaporating during the drying stage. Ma et al [2020] reported that, when slag is fully used as raw material, the increase in alkali content would lead to an increase in the characteristic pore size and a decrease in the total porosity. La concentration d'activateurs alcalins a également une grande influence sur les structures des pores en raison du changement de l'étendue de la géopolymérisation et de la teneur en eau [Chen et al, 2022].…”
Section: Effect Of Sludge Dewatered and Stabilized By Hydrated Lime O...mentioning
confidence: 99%
“…For the CFD-DEM method: determining the fluid properties and particle material characteristics parameters is a prerequisite to ensure accurate calculations. Here we refer to the relevant literature [8] to obtain the particle and fluid related parameters. As shown in Table 1.…”
Section: Flowing Slurry Materials Parametersmentioning
confidence: 99%
“…Chen X et al [7] found that the bend at the gas and solid two-phase flow pipeline is the most serious part of the erosion damage. Based on the above related research [8], this paper takes the bend pipe and uphill pipe sand slurry pumping project as the background, and studies the dynamics of slurry and fine pipe internal performance by CFD-DEM method, and analyzes the relevant parameters to understand the whole process of granular flow pumping in bend pipe with slope.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [27] established the relationship between the sample distribution characteristics and dissipated energy under impact loading. Ma et al [28] discussed the relationship between fractal dimension and compressive strength and found that the compressive strength of the material increased as the fractal dimension increased.…”
Section: Introductionmentioning
confidence: 99%